Exploring secondary school students' motivation using technologies in teaching and learning mathematics - Abu Bakar, Kamariah; Mohd Ayub, Ahmad Fauzi; Wong, Su Luan; Ahmad Tarmizi, Rohani (Elsevier, 2010)
The use of technology in teaching and learning mathematics has become more essential especially with the availability of new mathematics software or softwares that are downloadable for free from the internet. This paper looked into students’ motivation when using the V-Transformation courseware and an open source software, GeoGebra. The instrument used in this study was based on the ARCS model which consisted of attention, relevance, confidence and satisfaction components. Finding showed that there was a significant difference in the students’ attention using V-Transformation (M=4.05, SD= .811) compared to using GeoGebra (M=3.66, SD= .445; t(69)=2.514, p=0.014). Significant difference also was identified for the relevance component after using the V-Transformation (M=3.89, SD= .609) and GeoGebra (M=3.52, SD= .559; t(69)=2.641, p=0.001). However, no significant differences were found in students’ confidence and satisfaction using V-transformation and also GeoGebra software. For overall motivation, the finding showed that there was a significant difference between the motivation of students using V-transformation (M=3.78; SD = 0.403) as compared to the GeoGebra (M= 3.50; SD= 0.458; t(69)= 2.704, p=0.009). This finding suggested that technology could be used to motivate students in teaching and learning mathematics.